Distributed data storage and transmission for space Internet of things - Qinyu ZHANG; Shushi GU; Ye WANG; Jiayin XUE (物联网学报)
Based on the concepts and related techniques of Internet of things (IoT),tracking the development tendency of the satellite IoT and LEO constellation communication system abroad,and the deployment of the integrated satellite-terrestrial information network in China,the concept of space Internet of things (Space IoT) with its framework and main characteristics was proposed.Space IoT has the different concept compared to the traditional IoT,not just using the relay satellite to implement remote machine-to-machine communication.Space IoT is a ubiquitous IoT system under the integrated satellite-terrestrial information network architecture,and an expansion of the terrestrial IoT in the global three-dimensional world,and a service and application platform of multiple information technologies.With the recently era of big data,the space IoT has to face some data storage and transmission problems,such as excessive system load,data loss,frequent link interruption,high energy consumption,etc.Establishing a space-oriented IoT integrated distributed storage and transmission system was to meet the requirements of security guarantee and cross-domain interconnection with massive information businesses.Development status of related technologies were illustrated.At last,the prospect and thought of the future research of space Internet of things were presented.